Platelet phenotypes and practical aspects of platelet function testing in cardiology - Zh. D. Kobalava; A. S. Pisaryuk; A. A. Filkova; E. S. Tukhsanboev; A. A. Boldyreva; D. P. Lazutova; I. A. Meray; M. A. Panteleev (Рациональная фармакотерапия в кардиологии, 2023)
The assessment of platelet dysfunction is usually used by hematologists to diagnose inherited (such as Bernard-Soulier syndrome, platelet-type-von Willebrand disease, Glanzmann thrombasthenia, etc.), and acquired (symptomatic) platelet disorders (in hemoblastoses, uremia, liver cirrhosis, etc.), as well as to predict the risk of intraoperative bleeding in these groups of patients. Later, laboratory platelet function tests began to be used by cardiologists, first in experimental and clinical studies. In further years, attempts were made to introduce them into clinical practice. Current data show association between platelet hyperreactivity and pathogenesis of cardiovascular events. At the same time, despite the various consensus papers on assessing thrombotic and bleeding risk, monitoring antiplatelet therapy, including those published by Russian experts, in practice there are many subtleties and questions about the practical aspects of using laboratory tests. In addition, the definition of platelet phenotype does not have a clear concept. The review purpose was to describe laboratory methods for assessing the platelet function, to give more information to cardiologists about its practical value and to understand what basic scientists and physicians mean by the term “platelet phenotype”.